Revolutionizing Financial management: Unleashing the power of AI for Sustainable Growth - Bhokare Arati S.; Patil Snehal D.; Kulkarni Praveen. M. (ITM Web of Conferences)
By cultivating more sustainable, effective, and efficient corporate practices, artificial intelligence (AI) reinvents financial management. Contemporary finance includes AI as an existential component. The cornerstone technology of the industrial revolution and technological revolution is artificial intelligence. The rise of artificial intelligence (AI) is reshaping financial management by transforming how firms make choices, allocate resources and control risk. As companies face increasing pressure to integrate sustainability into their operations artificial intelligence (AI) has emerged as a key tool for resolving complex environmental concerns and improving financial performance. AI-powered analytics can help businesses detect and assess ecological issues, optimize resource allocation, and speed up financial processes like forecasting, auditing, and budgeting. This strengthens decision-making and increases operational efficiency by providing real-time insights on ESG (Environmental, Social, and Governance) factors. AI also helps businesses, investors, and creditors. This research paper explores the literature on the transformative Power of AI in financial management, examining its role, applications, benefits, and challenges. It investigates AI’s impact on financial forecasting, portfolio optimization, risk management and compliance.